Hypoglycemic potential of genus Ficus L.: A review of ten years of Plant Based Medicine used to cure Diabetes (2000-2010) - Kiran Yasmin Khan, Mir Ajab Khan, Mushtaq Ahmad, Imran Hussain, Paras Mazari, Hina Fazal, Barkat Ali, Ibtesaam Zaima Khan (Journal of Applied Pharmaceutical Science)
Medicinal plants play an important role in cure of Diabetes mellitus all over the world. The aim of this paper is compile data to investigate the effects of plant extract, compounds and active constituents against diabetes. The present review is therefore, an effort to give specifically literature on the pharmaceutically important species of genus Ficus L. (Moraceae) with anti diabetic properties, reported in the literature from 2000-2010. Our literature survey showed that there is no comprehensive and systematic data on genus Ficus with particularly emphasis on antidiabetic potential based on clinical trials is published elsewhere. There are about 850 species of genus Ficus worldwide and among them only 6 species reported to use against diabetes. The profile presented includes its methodology used and their bioactive agents with anti diabetic activity. The species of genus ficus include: Ficus bengalensis L., Ficus carica L., Ficus racemosa L., Ficus hispida L. f., Ficus microcarpa L.f., and Ficus religiosa L. Among these, Ficus microcarpa L. f., and Ficus hispida L.f., are incorporated first time in this review to be used against diabetes by using experimental animals. Based on biochemical and histological findings, it can be concluded that these plants may develop the healing action of diabetic complications and reflected anti diabetic potential through its glucose lowering activity in alloxan or streptozotocin induced diabetic laboratory animals.
Keywords: Ficus, Diabetes mellitus, Hypoglycemic, Hyperglycemic, Blood glucose.